A review on food values of selected tropical fruits' seeds - Raihana, A. R. Noor; Marikkar, Mohammed Nazrim; Amin, I.; Shuhaimi, M. (Taylor and Francis, 2015)
Fruit seeds are usually thrown out as waste during processing or after human consumption. Over the years, researchers have dedicated their effort to assess the food and nutritional values of many different fruit seeds. In this review, the research findings releated to the food values of ten different fruit seeds namely, guava, pumpkin, papaya, honeydew, mangosteen, rambutan, water melon, mango, durian were discussed. For several fruit seeds, the macro nutrient components such as oil, protein, and carbohydrate of are found to vary due to either varietal defferences or geographical variations. Among the seeds discussed, the range of oil content was from 1.8% to 49.0% while the range of protein content was from 6% to 40.0%. While the high oil bearing fruit seeds are potential new sources of oil, those with high protein content can be used for recovery of protein. As some of fruit seeds are edible and found to possess a host of phytonutrients, they can be harnessed for medicinal purposes.This review concludes that utiliztion of fruit seeds could not only bring health and wealth but also help to minimize the waste disposal problem of agro-based industries.